Gamified Literacy Applications and Reading Proficiency Among Struggling Primary Learners in Indonesia: A Cluster Randomized Controlled Trial - Arief Ardiansyah; Irhamuddin; Muhammad Odi Tondi Nasution (Jambi Tuah Tengganai, 2026)
Foundational literacy among Indonesian primary learners remains critically low, with PISA 2022 reading scores far below OECD averages, yet rigorous evidence on gamified digital interventions in this context is sparse. This cluster-randomized controlled trial evaluated whether a structured, gamified literacy application (LiterasiKu) improved reading proficiency and for whom the effects were largest. We randomly assigned 24 schools (950 Grade 2–3 students) across three West Java districts to either 16 weeks of daily 30-minute LiterasiKu sessions integrated into regular instruction or standard Kurikulum Merdeka teaching. Three-wave Early Grade Reading Assessment data (baseline, midline, endline) were analyzed using hierarchical linear models with school random effects. The intervention produced medium-to-moderate effects on oral reading fluency (d = 0.58), phonemic awareness (d = 0.52), and reading comprehension (d = 0.47). Growth trajectory analyses showed sustained gains without attenuation across 16 weeks, countering novelty-driven explanations. Exploratory subgroup analyses revealed larger effects for lowest-quartile learners (d = 0.74 for fluency), suggesting equity potential, though regression-to-the-mean and floor effects remain alternative accounts. Implementation fidelity averaged 87.3% with modest teacher training. The findings demonstrate that culturally adapted gamified packages can deliver meaningful literacy gains within existing LMIC primary school timetables. However, without an active digital comparator, attribution to gamification mechanics remains unresolved. Future dismantling trials should isolate gamification from adaptive personalization components, followed by cost-effectiveness analyses before scaling decisions are made.